Exploring the relationship between obstetric violence, postpartum depression, and breastfeeding through structural equation modelling: evidence from 2015 Pelotas birth cohort - Marilia Arndt Mesenburg; Emanuele Souza Marques; Tatiana Henriques Leite; Maria do Carmo Leal; Mariangela Freitas Silveira (BMC Public Health)
Abstract Background Obstetric violence is a gender-based violence against women perpetrated by health professionals during pregnancy and childbirth and presents negative consequences for women and newborns. Our objective was to evaluate the effect of obstetric violence on breastfeeding and the role of postpartum depression as a mediator. Methods We analysed data from 4275 women and their newborns enrolled in the Pelotas 2015 Birth Cohort by type of delivery (vaginal and c-section). We performed structural equation modelling. The exposure to obstetric violence during childbirth was a latent variable, and the outcome was the duration of breastfeeding. We evaluate postpartum depression as a possible mediator of that relationship. Results Women who suffered obstetric violence presented a higher probability of interrupting breastfeeding earlier than those who did not. This effect was observed only among women who had vaginal delivery (-0.224; p value: 0.017). We did not find an effect of obstetric violence on breastfeeding among women who had c-section deliveries. The effect of postpartum depression as a mediator on the relationship between obstetric violence and breastfeeding was not demonstrated. The total effect (direct + indirect effect) among women who had vaginal delivery was − 0.223, p value: 0.016. The total effect for the c-section group did not attain statistical significance. Conclusions The occurrence of obstetric violence decreases the duration of breastfeeding among women who have vaginal births. We were unable to demonstrate the same effect among the c-section group. We did not identify postpartum depression as a mediator of the association studied. This is the first study to evaluate the role of postpartum depression as a mediator of the association between obstetric violence and breastfeeding and the second to evaluate this relationship. Further studies must be conducted to better understand this subject.